2019
DOI: 10.1002/pd.5453
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial function in fetuses with lower urinary tract obstruction: Is there a cardiac remodeling effect due to renal damage?

Abstract: Objectives: Cardiac remodeling due to renal dysfunction may have an impact on myocardial function (MF) of fetuses with lower urinary tract obstruction (LUTO).The aim was to identify possible differences in MF in LUTO fetuses compared with healthy controls and to look for interactions between urine biochemistry and MF indices.Methods: This is a cohort study consisting of 31 LUTO fetuses and 45 healthy controls. Subgroups were generated according to intrauterine therapy (group 1: LUTO after therapy, group 2: LUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Cardiac geometry in fetuses with LUTO showed an increased C/T ratio and ventricular hypertrophy, similar to previous reports [6,7]. RV diastolic dysfunction in fetal LUTO was previously observed, reflected as a decreased tricuspid valve E/A ratio [6] and a longer RV isovolumetric relaxation time [8]. LV diastolic dysfunction was previously demonstrated as a shorter mitral valve (MV) inflow time and higher LV MPI [7].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Cardiac geometry in fetuses with LUTO showed an increased C/T ratio and ventricular hypertrophy, similar to previous reports [6,7]. RV diastolic dysfunction in fetal LUTO was previously observed, reflected as a decreased tricuspid valve E/A ratio [6] and a longer RV isovolumetric relaxation time [8]. LV diastolic dysfunction was previously demonstrated as a shorter mitral valve (MV) inflow time and higher LV MPI [7].…”
Section: Discussionsupporting
confidence: 87%
“…Cardiomegaly, pericardial effusion and ventricular hypertrophy are common in fetal LUTO [6][7][8]. Right ventricular filling compliance, such as a decreased tricuspid valve E/A ratio [6] and longer right ventricular isovolumetric relaxation time [8], as well as a worse left ventricular myocardial performance index [7], have been noted. To date, there are no detailed data on the characteristics of myocardial deformations in fetuses with isolated LUTO.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that RV s' velocity was significantly higher in LUTO with LUTO as compared to controls. effect of the angiotensin release in LUTO foetuses remains to be confirmed [8].…”
Section: Discussionmentioning
confidence: 93%